An Analysis of Politeness Strategies Used by the Main Characters in the Intern (2015) - Ardi Yansyah Yakub Langoday; Nurma Dhona Handayani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This research aims to analyze the use of politeness strategies used by the main characters in the movie The Intern (2015) based on Brown and Levinson’s politeness theory (1987). This study applies a qualitative descriptive method, and the data are taken from the movie dialogues. The data analysis focuses on four types of politeness strategies, namely bald on-record, positive politeness, negative politeness, and off-record strategies. The findings show that all four strategies are used in the movie with different functions depending on the context and the relationship between the speakers. Bald on-record is mostly used in direct and urgent situations, positive politeness is used to build closeness and solidarity, negative politeness is applied to show respect in formal interactions, and off-record strategy is used to express meaning indirectly to avoid conflict. This study concludes that politeness strategies play an important role in creating effective communication in workplace interactions. This research is expected to contribute to the study of pragmatics, especially in understanding politeness strategies in professional communication.